2020
DOI: 10.1002/agr.21675
|View full text |Cite
|
Sign up to set email alerts
|

Who practices urban agriculture? An empirical analysis of participation before and during the COVID‐19 pandemic

Abstract: Coronavirus disease‐2019 (COVID‐19) disrupted the food system motivating discussions about moving from a dependence on long food supply channels toward shorter local supply channels, including urban agriculture. This study examines two central questions regarding the adoption of urban agriculture practices at the household level during the COVID‐19 pandemic: whether the outbreak of the novel coronavirus elicited participation in urban agriculture (e.g., community growing and home growing) and what are the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 24 publications
2
36
1
1
Order By: Relevance
“…However, the gardens were minimally maintained, and none were permanently closed due to the work of a few volunteers. Similarly, in Detroit and Phoenix metropolitan areas, in the United States, researchers found that, during the pandemic, there was a decrease in community garden participation, in which lower-income households were more likely to participate, whereas younger and highly educated males engaged in home food growing [26].…”
Section: Discussionmentioning
confidence: 98%
“…However, the gardens were minimally maintained, and none were permanently closed due to the work of a few volunteers. Similarly, in Detroit and Phoenix metropolitan areas, in the United States, researchers found that, during the pandemic, there was a decrease in community garden participation, in which lower-income households were more likely to participate, whereas younger and highly educated males engaged in home food growing [26].…”
Section: Discussionmentioning
confidence: 98%
“…Apart from being a means of early education for children (Chenarides et al, 2021;Khan et al, 2020) during distance learning activities, encouraging women's participation (Azunre et al, 2019;Khan et al, 2020), and creating biodiversity (Galimberti et al, 2020), this green space effort can realize sustainable urban development (Adidja et al, 2019;Ibrahim & Salim, 2020;Khan et al, 2020;Li et al, 2020b;Yusoff et al, 2017). It was different from before the pandemic, where urban agriculture was dominated by working family and a larger number of household (Chenarides et al, 2021). In Montreal, urban Canadian agriculture is still dominated by well-educated and high-income family groups (Bellemare & Dusoruth, 2020).…”
Section: Visual Perception On Urban Agriculturementioning
confidence: 99%
“…Therefore, through its extension workers, the government can provide resources and motivation for the community to like gardening starting from the yard, especially for people constrained by time and resources (Chenarides et al, 2021), besides maintaining the remaining agricultural land. Meanwhile, millennials can develop urban agriculture with more modern technology, such as hydroponics and verticulture techniques (Lal, 2020;Martin & Molin, 2019), so that the stereotypes around farming such as being messy and dirty can be reduced.…”
Section: Research Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence of HFP activities since the start of the COVID-19 pandemic is limited, though our previous work found about half of respondents reported producing, foraging, hunting, or canning last year and nearly one third were engaging in those activities at the time of the survey [39] (Belarmino et al, 2020). Chenarides et al (2020) [40] examined urban gardening before and during the COVID-19 pandemic, finding lower participation in community gardens as compared to at-home gardens. Constant et al (2020) found having a garden/terrace positively associated with unhealthy behaviors during the COVID-19 lockdown in France, primarily a reduction in physical activity.…”
Section: Introductionmentioning
confidence: 99%